231 ESTABLISHING AN INTERVENTIONS BUNDLE TO IMPROVE INPATIENT CARE FOR PATIENTS WITH PARKINSON'S DISEASE: A MULTIDISCIPLINARY QUALITY IMPROVEMENT PROJECT. (18th November 2021) - Penugonda, M; Walsh, J; Barry, J J; Govern, R M; Bradley, D; Bolger, M; English, G; Moore, J; Nolan, N; Treacy, E; Burke, J; Dwyer, N; et al.
Abstract: Background: Patients with Parkinson's (PwP) are at a higher risk of complications once admited to hospital compared to their age-matched peers. Medication mismanagement is a well-known obstacle, which puts PwP at risk of sub-optimal treatment leading to an unnecessary deterioration of baseline and potentially increases risk of adverse sequelae. Methods: Retrospective electronic patient records (EPR)/chart review of 47 admissions was conducted, across three hospital sites. Data attaining to correct prescribing of medication on admission and discharge, prescribing of contraindicated medications, reasons for medication lapses and complications of inpatient stay were collected. EPR of 17 patients' were reviewed to assess if Parkinson's disease (PD) medication administrations occurred within 30 minutes of patient schedule, as recommended by NICE guidelines. Key areas for improvement were identified based on the results. Results: 47 charts (30 Males, 17 Females) with mean age 72 (range:57–90), were reviewed. Average number of co-morbidities:4.5 and Clinical Frailty Scale ranged 5–9 (n = 30). LOS averaged 12.4 days and 43% of patients had ≥2 hospital admissions in the preceeding year. 38% (17/44) of admissions correctly documented patient specific medication times. Only 48% of patients (n = 638) received their medications within 30 minutes of the scheduled time. 47% (22/47) experienced complications attributable to PD. Contraindicated medications were noted in 5 cases. 84% of discharging prescriptions did not mention timing of PD medication and 3 prescriptions had errors with regards to dosage/omission of medication. Conclusion: We implemented across two sites: 1) Care protocol flag in patient's chart highlighting simple avoidable complications. 2) Laminated over the bed signpost alerting 'time critical medication'. 3) 'Time critical medication' stickers in drug kardex 4) Education sessions for Medical, Nursing and Ward staff. 6) Establishing out of hours access to PD medications and protocols for NPO/poor swallow. We plan to reassess significance of efforts post intervention.